6+2(x-5)=2(-x+4)

Simple and best practice solution for 6+2(x-5)=2(-x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2(x-5)=2(-x+4) equation:


Simplifying
6 + 2(x + -5) = 2(-1x + 4)

Reorder the terms:
6 + 2(-5 + x) = 2(-1x + 4)
6 + (-5 * 2 + x * 2) = 2(-1x + 4)
6 + (-10 + 2x) = 2(-1x + 4)

Combine like terms: 6 + -10 = -4
-4 + 2x = 2(-1x + 4)

Reorder the terms:
-4 + 2x = 2(4 + -1x)
-4 + 2x = (4 * 2 + -1x * 2)
-4 + 2x = (8 + -2x)

Solving
-4 + 2x = 8 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-4 + 2x + 2x = 8 + -2x + 2x

Combine like terms: 2x + 2x = 4x
-4 + 4x = 8 + -2x + 2x

Combine like terms: -2x + 2x = 0
-4 + 4x = 8 + 0
-4 + 4x = 8

Add '4' to each side of the equation.
-4 + 4 + 4x = 8 + 4

Combine like terms: -4 + 4 = 0
0 + 4x = 8 + 4
4x = 8 + 4

Combine like terms: 8 + 4 = 12
4x = 12

Divide each side by '4'.
x = 3

Simplifying
x = 3

See similar equations:

| i/50+2=144 | | 3x-(4-2x)-5=26 | | y=6x-300 | | y=0.50(10)+3 | | y=0.50(5)+3 | | 7/8x=49 | | 10x-8=6x-4 | | y=7(3)+10 | | 3t^2-8=19 | | 42x=5x(10x-4) | | F/5-11=-11+9/10f | | (x-4)/(9x-36) | | X+106=x+86 | | 8+7x=22x-2 | | -(91p+35q-40)= | | 4y=16x+8 | | 1x-3=5 | | 3.47+19.36=10.22 | | 26x-5=25x | | x-3y=-29 | | 9x+4y-6z=6 | | 14x+8=-1+15x | | -2x^2+10x-8=0 | | b=p+3a+3c | | 1x+3(6x-30)=-14 | | 7/8X-2=-15/16X+3 | | 3y^2-9=0 | | 3x+1/4=2x-6/2 | | 3(s-13)+2(s-7)=7 | | 3(t-13)+2(t-7)=7 | | 16x-3(43x)=8 | | 3+2(s-2t)= |

Equations solver categories